Delayed-Onset Seizures Following Self-Inflicted Nail Gun Injury to the Head: A Case Report and Literature Review - Hoey, Alexander; Troy, Christopher; Bauerle, Wayne; Xia, Anthony; Hoey, Brian (Journal of Neurological Surgery Reports, 2022)
Nail gun use and its associated incidence of injury have continued to increase since it was first introduced in 1959. While most of these injuries involve the extremities, a subset of patients suffer intracranial trauma. The most recent comprehensive review on this particular subject referenced 41 cases and advocated for further discussion regarding proper treatment plans for these individuals. We present the case of a 25-year-old who suffered 35 self-inflicted penetrating head wounds from a nail gun after suffering an amputation injury at his job site. No neurological deficits were present on his arrival to the emergency room. He underwent surgery to treat his arm wound and remove 13 of the 35 nails. The patient was discharged from the hospital on levetiracetam and made a full recovery. Nearly 1 year later, he experienced a seizure at his workplace. However, after resuming his antiepileptic medication, he reports no further complications. This case is distinct for not only being the most nails in a patient's head at presentation, but also following surgery. Utilizing this case, prior review, and 27 subsequent cases, we propose an updated algorithm for diagnosis and treatment of nail-gun-related penetrating head trauma.
Keywords: nail gun; penetrating head trauma; intracranial injury